Resveratrol: Extraction Techniques, Bioactivity, and Therapeutic Potential in Ocular Diseases - Giulia Accomasso; Flavia Turku; Simona Sapino; Daniela Chirio; Elena Peira; Marina Gallarate (Scientia Pharmaceutica, 2024)
Resveratrol (RV), a natural polyphenol found in various plants, exhibits a wide range of bioactive properties and mechanisms of action. Its potential therapeutic benefits in several diseases and, more specifically, in ocular diseases have garnered significant attention, with studies exploring RV properties at cellular, molecular, and physiological levels. Like many natural derivatives, RV can be obtained through various extraction methods from plant sources, with a growing interest in sustainable techniques that align with recent trends in sustainability, circular economy, and green chemistry. This review begins by describing the most efficient and sustainable extraction techniques of RV from natural sources and then delves into its numerous bioactive properties and its synergistic effects with other active substances and drugs. Furthermore, an overview of the scientific literature on RV as a therapeutic agent for ocular diseases, both in its pure form and entrapped in nanoparticulate systems, is provided.